Reporting quality of music intervention research in healthcare: A systematic review. (June 2018) - Robb, Sheri L.; Hanson-Abromeit, Deanna; May, Lindsey; Hernandez-Ruiz, Eugenia; Allison, Megan; Beloat, Alyssa; Daugherty, Sarah; Kurtz, Rebecca; Ott, Alyssa; Oyedele, Oladele Oladimeji; Polasik, Shelbi; Rager, Allison; et al.
Highlights: Publications of music intervention research are increasing, as are concerns about inadequate reporting and inconsistent terminology. Less than 50% of published studies provide enough detail about the music intervention, inhibiting interpretation and cross-study comparisons. Credentialed music therapists and registered nurses deliver most music interventions, with clear differences in both content and delivery. Terminology describing music interventions is inconsistent and at times misapplied creating barriers to interprofessional communication. Recommend investigators use Checklist for Reporting Music-Based Interventions to improve reporting quality, rigor, and clinical relevance. Abstract: Introduction: Concomitant with the growth of music intervention research, are concerns about inadequate intervention reporting and inconsistent terminology, which limits validity, replicability, and clinical application of findings. Objective: Examine reporting quality of music intervention research, in chronic and acute medical settings, using the Checklist for Reporting Music-based Interventions. In addition, describe patient populations and primary outcomes, intervention content and corresponding interventionist qualifications, and terminology. Methods: Searching MEDLINE, PubMed, CINAHL, HealthSTAR, and PsycINFO we identified articles meeting inclusion/exclusion criteria for a five-year period (2010–2015) and extracted relevant data. Coded material included reporting quality across seven areas (theory, content, delivery schedule, interventionist qualifications, treatment fidelity, setting, unit of delivery), author/journal information, patient population/outcomes, and terminology. Results: Of 860 articles, 187 met review criteria (128 experimental; 59 quasi-experimental), with 121 publishing journals, and authors from 31 countries. Overall reporting quality was poor with <50% providing information for four of the seven checklist components (theory, interventionist qualifications, treatment fidelity, setting). Intervention content reporting was also poor with <50% providing information about the music used, decibel levels/volume controls, or materials. Credentialed music therapists and registered nurses delivered most interventions, with clear differences in content and delivery. Terminology was varied and inconsistent. Conclusions: Problems with reporting quality impedes meaningful interpretation and cross-study comparisons. Inconsistent and misapplied terminology also create barriers to interprofessional communication and translation of findings to patient care. Improved reporting quality and creation of shared language will advance scientific rigor and clinical relevance of music intervention research.